Development of Quartet Card Media on Changes of State of Matter Materials in Class IV of State Elementary School 34 Banyuasin III - Nila Sari; Yusni Arni; Hotma Minar Lubis, Patricia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This paper presents research on the development of learning media in the form of cards, aiming to create a set of cards learning media that can be tested for validity and practicality in learning. This research is a developmental study (Research and Development) utilising the Robert G. March model, specifically the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework, employing data collection techniques in the form of questionnaires and documentation. Based on the research results, the quartet card learning media is declared valid and tested to be efficient by the three validators, with the results of 82% media expert validation, 86% material expert validation, and 82% language expert validation, with a very valid category. The practicality trial indicates the one-to-one trial with 84.5% with a very feasible category, the small group trial with 86.3% with a very feasible category, and the last practicality trial refers to the real class with an average of 85% with a very feasible category. Therefore, the quartet card media is very feasible to use.